Efficacy of oclacitinib for the control of feline atopic skin syndrome: correlating plasma concentrations with clinical response. Issue 8 (August 2022) - Carrasco, Isaac; Ferrer, Lluis; Puigdemont, Anna
Objectives: The aim of this study was to assess the efficacy of a new therapeutic regimen of oclacitinib for the control of feline atopic skin syndrome (FASS) and to correlate plasma levels of this drug with clinical effects. Methods: Twenty-eight client-owned cats with a clinical diagnosis of FASS were recruited. Oclacitinib was administered at 1 mg/kg q12h for 2 weeks and then at 1 mg/kg q24h for a further 2 weeks. At the study outset (D0), and 7 (D7) and 28 (D28) days after starting treatment, clinical lesions were assessed using a validated scoring system (SCORing Feline Allergic Dermatitis [SCORFAD]) and pruritus was graded via an adapted visual analogue scale (PVAS). At the same time points, plasma oclacitinib levels and haematological variables were measured. Results: Among 18 cats completing the study, PVAS and SCORFAD improved by ⩾50% in 61% and 88% of animals, respectively. Mean PVAS decreased significantly between D0 and D7 and between D0 and D28 (both P <0.001) but not between D7 and D28. Likewise, mean SCORFAD values decreased significantly between D0 and D7 and between D0 and D28 (both P <0.001) but not between D7 and D28. On D7 and D28, plasma oclacitinib concentrations varied widely from 0 to 1443.2 ng/ml and from from 0 to 1177.7 ng/ml, respectively. Oclacitinib concentrations showed no correlation with clinical effects (SCORFAD and PVAS). Conclusions and relevance: Oclacitinib emerged as being safe and effective to control clinical signs of FASS. A mean dose of 1 mg/kg, even without extending twice-daily treatment beyond the first 2 weeks, could be a suitable therapeutic regimen. Plasma drug levels did not seem useful to predict clinical response during treatment.